Development and optimization of an aerodynamic device for the UA Formula Student car - Novais, Pedro Miguel Gaspar (2021)
The development and optimization of the rear wing of a Formula Student car must be done with the aid of CFD numerical simulations, since in order to ensure a good aerodynamic performance a great number of wing configurations need to be tested. The aim of this thesis was to develop a fully functional optimization code, that could be easily adapted to generate the optimal rear wing for any given Formula Student car, only needing the car CFD results. As a means to accomplish that, a CFD simulation was performed to the Formula Student Aveiro teams’ car and additional wind tunnel testing was conducted with the purpose of corroborating the simulation results. Hereupon, the velocity profile at the car rear end, obtained in the CFD simulation, was used as the inlet in the rear wing simulation for the optimization process, allowing a contribution of the car geometry to the rear wing optimization without the addition of unnecessary computational time. Finally, an optimization code based on the Harmony Search Algorithm was created to define the optimal rear wing parameters and with that achieve an optimized rear wing configuration. The optimized configuration consists of 4 airfoils, and showed excellent results even surpassing the rear wing performance of the 2016 FSAE Czech Republic competition winner.